Advances in Universal Web Design and Evaluation: Research, Trends and Opportunities - Kurniawan, Sri; Zaphiris, Panayiotis (My University, 2007)
As the Internet has become more pervasive, information disseminated through the Web grows in an exponential rate, creating a call for more universal design so more people from different backgrounds are able to access this information. Advances in Universal Web Design and Evaluation: Research, Trends and Opportunities covers various aspects of universal Web design from disabilities to cultural differences, including various aspects of Web design: prototyping, analysis, and evaluation with an emphasis on universal and inclusive design. Advances in Universal Web Design and Evaluation: Research, Trends and Opportunities highlights several prominent issues in this area such as ageing and gender issues and provides the basis of a framework for the development and evaluation of Web sites for people with special needs.